Student Behaviours from Large Classes in Tanzania Secondary Schools: A case of School Y in Morogoro Municipality - Fumito, Irene R.; Kinyaduka, Bryson Daudi (Journal of Education and Practice, 2025)
Purpose: The purpose of the study was to explore student behaviours in large classes. The study intended to establish student behaviours developing from large classes in a selected school in Tanzania. Methodology: The study adopted a single case study design. The study collected data through semi-structured interview and unobtrusive observation. The data were collected from ten participants, and through unobtrusive observation of classes. Findings: Student behaviours developed from large classes were: stealing, lying and hiding, laziness, getting late in classes, and truancy among others. Unique Contribution to Theory, Policy and Practice: There are diverse student behaviours from large classes. The student behaviours in large classes are contextual and/or circumstantial. Most of student behaviours from large classes are rare in the existing literature. Further, large classes have unpopular nurturing effects to student behaviours. The student behaviours may last in life time after graduation. Teachers need capacity building on managing large classes to minimize unpopular nurturing effects from large classes.